Character Education in Contemporary Islamic Thinking - Irmansyah; Andi Maryam Azis (ETDC: Indonesian Journal of Research and Educational Review, 2021)
Character education is education to shape one's personality through character education, the results of which can be seen in one's real actions, namely good and honest behavior, being responsible, respecting the rights of others, hard work, and so on. Good character means knowing the good, loving the good, and doing the good. Contemporary Islamic thought generally makes episteme, reason, 'aqal, khitab, or paradigm, which is understood as the basis for the growth and development of science and tradition, the object of their thinking. This paper will present one of the efforts to improve character education in contemporary Islamic thought. It will namely present the concept of the leading philosophical thought, namely Ibn Sina, and its implications for today's Islamic education. Ibn Sina divides the level of scientific material that must be passed by students based on the stage of development and age of the child's growth into, among others, Ages 3 (three) to 5 (five) Years, Ages 6 (six) to 14 (fourteen) Years, and Ages 14 (fourteen) and Over.